ASSISTANCE IN FORMULATING AFFECTIVE AND EFFICIENT SUBJECT SCHEDULES THROUGH THE TIMETABLE APPLICATION AT SMA 1 NISAM - Bahri, Samsul; Saputra, Eri; Husna, Asmaul (Universitas Muhammadiyah Aceh, 2021)
Community service aims to mentor teachers of SMA N 1 Nisam in the preparation of teaching schedules through timetable applications. TimeTable is an application created specifically to help users organize schedules, which are more affective and efficient. TimeTable has an elegant look so it's easy to operate. The application of asc time table will make it easier to work on the curriculum, especially for the preparation of the schedule of subjects quickly, accurately and relevantly, and can overcome the problems of clashing schedules of subjects perclass, teacher, and study room at SMA N1 Nisam.Key words: TimeTable, Course schedule